INCOME STRATIFICATION OF THE POPULATION AND OPPORTUNITIES TO INCREASE INCOMES - GANIEV, MUHAMMADJON (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article analyzes the sources of population incomes, the purchasing power of incomes, the stratification of incomes and its variability in the conditions of the market economy.